Pembelajaran Elemen Gerak Tari Menggunakan Model ARCS di SMP Negeri 1 Sumberjaya Lampung Barat - Ita Ani Rosita; I Wayan Mustika; Susi Wendhaningsih (Jurnal Seni dan Pembelajaran, 2019)
This study aims to describe the use of learning models of attention, relevance, confidence, satisfaction (ARCS) in the learning of dance movement elements in SMP Negeri 1 Sumberjaya, West Lampung. This type of research is qualitative descriptive. Data collection techniques in this study are observation, interviews, and documentation. Data sources are cultural arts teachers and 32 students in class VII A. The teacher carries out dance movement learning elements based on 7 steps and 4 principles of the ARCS learning model. The seven steps are reminding students of the concepts that have been learned, conveying the goals and benefits of learning, conveying the subject matter, using concrete examples, providing tutoring, giving opportunities for students to participate in learning, providing feedback. Step by step, the four principles, namely attention, relevance, confidence, satisfaction, are carried out along with the implementation of learning steps. Penelitian ini bertujuan untuk mendeskripsikan penggunaan model pembelajaran attention, relevance, confidence, satisfaction (ARCS) pada pembelajaran elemen gerak tari di SMP Negeri 1 Sumberjaya, Lampung Barat. Jenis penelitian ini ialah deskriptif kualitatif. Teknik pengumpulan data pada penelitian ini adalah observasi, wawancara, dan dokumentasi. Sumber data yakni guru seni budaya dan 32 siswa di kelas VII A. Guru melaksanakan pembelajaran elemen gerak tari berdasarkan 7 langkah dan 4 prinsip model pembelajaran ARCS. Ketujuh langkah tersebut yaitu mengingatkan kembali siswa pada konsep yang telah dipelajari, menyampaikan tujuan dan manfaat pembelajaran, menyampaikan materi pelajaran, menggunakan contoh-contoh yang konkrit, memberi bimbingan belajar, memberi kesempatan kepada siswa untuk berpartisipasi dalam pembelajaran, memberikan umpan balik. Sedangkan, keempat prinsip yaitu attention, relevance, confidence, satisfaction, terlaksana seiring dengan terlaksananya langkah-langkah pembelajaran.Kata kunci: Elemen Gerak Tari, Model ARCS, Pembelajaran